Kajian terhadap Hak Milik Atas Tanah yang Terjadi Berdasarkan Hukum Adat - Ilyas Ismail (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: In accordance to Article 22 Number 5, 1960 states that the ownership right of land can be issued based on customary law and the procedure of issuing the title right ruled by the law as regulated by Government Regulation. In fact, recently such regulation has not been enacted yet; hence it cause different views on issuing the ownership right of land. Therefore, the problem raised in this research are what is the legal basis regarding the issuance of the title right based on customary law and what is the position such right based on the issuance. To answer the questions, this research is conducted towards the legislation, doctrines, and previous researches that are relevant to this research. The research shows that the legal basis for the issuance of such right is the customary principles found in customary law, the value of customary law in the place. Substantially, the customary ownership right has similar position as ownership right issued based on government decision, the distinction is on the ownership right proof of certificate of the right that is issued based on government decision but the land owned by customary right namely physical owning evidence and the acknowledgement of the people living the in the place where the right issued.  The Study on Ownership Right of Land Issued Based on Customary Law